Universal Design for Learning and Instruction: Effective Strategies for Inclusive Higher Education - Rosa Espada-Chavarria; Rayco H. González-Montesino; José Luis López-Bastías; Miriam Díaz-Vega (MDPI AG, 2023)
Guaranteeing inclusive, high-quality education for all requires comprehensive changes to the curriculum so that, instead of creating or perpetuating barriers, these barriers are eliminated. Universal Design for Learning (UDL) and Universal Design for Instruction (UDI) emerge as teaching strategies that encourage inclusion in education. This study presents the implementation of both models within the higher education framework, applying them to the Spanish Sign Language and Deaf Communities degree that is studied by a large number of deaf students. For this purpose, a descriptive study is presented with a quantitative methodological approach using a survey as an instrument. Four dimensions were established for designing the curriculum: course materials, teaching strategies, synchronous course management, and asynchronous. After student assessment, the results revealed their high level of satisfaction and the importance these teaching strategies had for their motivation, comprehension, and learning of the relevant competencies. There was also recognition of the importance of blended teaching methods for active learning as a vehicle for increasing student involvement and participation. This study concludes that it is necessary to continue progressing in the practical implementation of teaching models based on Universal Design, which also supports course management.